The Role of Articulatory Phonetics in Improving Listening for the First-Year Students of English at Stiba Saraswati Denpasar - Denok Lestari (Bandar Lampung University (UBL), 2013)
Listening is prerequisite for oral proficiency and is recognized as fundamental skills. Through listening, students can build an awareness of the language systems and establish more fluent productive skills. This research is generally aimed to help the students of English improve their listening skills and develop their awareness on distinctive sounds which are not native to their mother tongue, as well as to help language teachers in designing the effective lesson plans for the listening courses. This study on the role of phonetics in language teaching is highly expected to develop better understanding in the target language and encourage native-like English pronunciation for Indonesian students.The findings showed that the students found difficulties in listening and pronouncing distinctive segments namely: /ʃ/, /ʒ/, /θ/, /ð/; long vowels /i:/, /a:/, /ɔ:/, /u:/, /3ː/; diphthongs /eI/, /әʊ/, /Iә/, /eә/, /ʊә/; and final clusters. The use of articulatory phonetics was proven to be effective in raising the students’ awareness in producing English sounds which differ in place and manner of articulation. It could be seen from the post-test results in which there were fewer students who made mistakes in listening and pronouncing distinctive sounds. The audio-lingual method was appropriate to the teaching of the aural skill as it employed listening-imitation-practice-production to teach English pronunciation.